Factor analysis of rules in friendship: relations with personality traits and friendship quality - Bubaš, Goran (Array, 2008)
This paper presents research conducted on the factor structure of rules in friendship relationships. Based on the previous research of other authors and the process of collecting the rules that young adults use in their friendship relationships, an IR-1 self-assessment measure was developed that consisted of 141 friendship-related rules which was applied on a large set of subjects (N=501) in the age of early adulthood. A factor analysis of the IR-1 items revealed five dimensions of rules in friendship relationships that were labeled benevolence, sociability, appropriateness, self-control, and self-directedness. The NEO PI-R inventory, which measures the personality dimensions according to the five-factor model of personality, was applied on a smaller subset of subjects (N=114) together with the IR-1 measure. Many statistically significant correlations were uncovered between the dimensions of interpersonal rules on the one hand, and the personality dimensions and their facets on the other hand, most of which were related to extraversion and agreeableness. The five uncovered factors of interpersonal rules were used for the development of a self-assessment instrument IRF-2 with 60 items and five subscales designed to measure the related dimensions of rules in friendship relationships. In addition, a brief measure of positive and negative aspects of friendship quality was developed and a correlation analysis was performed on a small convenience sample (N=61) between variables related to the dimensions of rules in friendships and the variables related to the quality of friendship with a best friend. The results indicated that the use of rules in friendship associated with the dimensions benevolence and sociability had the largest positive influence on the quality of friendship with a best friend.